Apakah Global Value Chain (GVC) Memengaruhi Permintaan Tenaga Kerja? Studi Empiris dari Industri Manufaktur Indonesia Tahun 2010–2015 - Ramana, Febria; Damayanti, Arie (National Research and Innovation Agency, 2024)
Participation in the Global Value Chain (GVC) encourages domestic industry development and increases productivity, expanding labour demand. However, theoretically, a firm’s participation in GVC can increase the labour demand through the scale effect and reduce the labour demand due to the substitution effect. This issue is relevant in Indonesia because the extent of GVC participation among firms in the manufacturing sector is still low. This study examines the correlation of GVC participation in the manufacturing subsector to labour demand. This study uses Asian Development Bank (ADB) calculations that divide manufacturing subsector GVC participation into three types, namely Pure Forward Participation (PFP), Two-Sided Participation (TSP), and Pure Backward Participation (PBP). The data used is panel data from 2010-2015, the Large and Medium Industry Survey conducted by Statistics Indonesia (BPS) and analysed using a linear dynamic model. The analysis found that in the short term, (i) PFP is positively correlated, (ii) TSP tends to be negatively correlated but not significant, and (iii) PBP is positively correlated but not significant. All three types of participation significantly affect labour demand in the long run. Therefore, manufacturing industry linkages in PFP and PBP must be improved to increase labour absorption in the manufacturing sector.